SIMULATION OF FLUID FLOW AND HEAT TRANSFER IN PORE MEDIUM BY USING LATTICE BOLTZMANN METHOD - WIJAYA ( NIM: 20214057 ) , IMAM
Fluid flow and heat transfer in pore medium is a kind of important phenomena to understand in geothermal reservoir, because this phenomena has directly corellation with electrical energy which can be extract from the reservoir. In this resaserch, I have been done simulate of fluid flow and heat transfer in pore medium by using Lattice Boltzmann Methode to understand the mechanism of fluid flow and heat transfer in geothermal reservoir. Lattice Boltzmann Metode is a kind of computational method base on Boltzmann equation, so the behavior of a group particles follow the Boltzmann distribution equation. In this research, the simulation conducted in 2D (D2Q9). To understand the fluid flow and heat transfer in reservoir, we varied the injected temperatur from the left wall of the reservoir and from the heat source(bottom reservoir). In the 1st experiment we set the injected temperatur 450C and the heat source 4100C, 2nd experiment we set the injected temperatur 102.50C and the heat source 4100C, 3rd we set the injected temperatur 307.50C and the heat source 4100C and also we set the parameter of reservoir such as : porocity, dencity, and injected velocity are constant. From the 1st experiment, known that the temperature distribution between experiment and simulation 92.86% are match. From the 2nd experiment, known that there is one pick of thermal distribution and one of turbulen zone, and from the 3rd experiment known that there are two pick of thermal distribution and two of turbulen zone.